Predation by Anthocoris minki pistaciae Wagner (Hemiptera: Anthocoridae) on Agonoscena pistaciae Burckhardt and Lauterer (Hemiptera: Psyllidae) at different temperatures - Mahshid Sarnevesht (Egyptian Journal of Biological Pest Control, 2018)
Abstract Pistachio is one of the most common tree nuts in Iran and in the world, and Agonoscena pistaciae Burckhardt and Lauterer (Hemiptera: Psyllidae) is propounded as a considerable pest of pistachio trees. Among the numerous predators, Anthocoris minki pistaciae Wagner (Hemiptera: Anthocoridae) was found as a common species in pistachio orchards of Kerman Province, Iran. The consumption rate index is essential to determine the prey-predator interaction and efficiency for biological control. On the other hand, temperature as an abiotic environmental factor has an important influence on population parameters of insects. Thus, predation rate of A. minki pistaciae feeding on A. pistaciae was evaluated at three different temperatures (17, 26, and 30 ± 2 °C) with a 16L:8D photoperiod and 55 ± 5% R.H. All of the data were analyzed by the age-stage, two-sex consumption rate, MS Chart software (Ver. 2017.05.28). Obtained results showed that the highest net predation rate (C 0) and the transformation rate from prey population to predator offspring (Q p ) occurred at 30 °C (1309.13 and 54.67 prey nymphs, respectively). Moreover, the highest value for the mean prey consumption of adult insects was (1300.15 psyllid nymphs) and the highest daily mean consumption rate was calculated at this temperature. Thereupon, 30 °C is the best temperature for feeding A. minki pistaciae under the laboratory conditions.